PENGARUH EXPERIENTIAL MARKETING DAN TRUST TERHADAP KEPUASAN PELANGGAN PENGGUNA KARTU AS TELKOMSEL PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS ABDURACHMAN SALEH SITUBONDO DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING - Yunus, Hedi; Kusnadi, Edy; Praja, Yudha (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The world of increasingly sophisticated technology makes the development of information and communication in the current era of globalization grow very rapidly, this is supported by people who rely heavily on technology in their daily activities. The purpose of this study is to analyze and test the effect of Experiential marketing and Trust on customer satisfaction of Telkomsel Kartu As users on students of the Faculty of Economics and Business, Abdurachman Saleh Situbondo University through buying interest. The sampling technique used was proportional stratified random sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model-Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that Experiential marketing is not proven to have a significant effect on Customer satisfaction, Experiential marketing has a significant effect on purchase intention, Trust has no significant effect on Customer satisfaction, Trust has a significant effect on buying interest. The results of the indirect effect hypothesis test show that the Experiential marketing variable on Customer satisfaction through buying interest has a significant positive effect, Trust on customer satisfaction through Buying interest has a significant positive effect.